Treatment of generalized pustular psoriasis with Spesolimab: a case report and literature review - Xiaoqian LIANG; Zexi MI; Yaohan XU; Yongfeng CHEN (Pifu-xingbing zhenliaoxue zazhi, 2024)
Objective To evaluate the efficacy and safety of Spesolimab in the treatment of generalized pustular psoriasis(GPP). Methods A 30 years old female with GPP was intravenously given 900 mg of Spesolimab once. The safety and the changes in modified generalized pustular psoriasis area severity index (GPPASI) and generalized pustular psoriasis physician global assessment (GPPGA) were evaluated. Results After 1 week of the treatment, the GPPGA reached 2. After 2 months of the treatment, pustules almost completely subsided and both GPPASI and GPPGA reached 1. During the treatment, the patient developed anaphylactic adverse reactions, which were improved following the injection of betamethasone, antihistamine and symptomatic therapy. Conclusion Spesolimab is an effective and safe agent for the treatment of generalized pustular psoriasis.